Analisis Faktor-Faktor yang Mempengaruhi Ekspor Ikan Segar Indonesia - Winna Yuliana; Zata Hasyyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
International trade plays a vital role in strengthening Indonesia’s economic growth, particularly through the export of fishery products which are among the country’s leading commodities. Fresh fish exports are highly influenced by external demand factors in destination countries as well as Indonesia’s own production capacity. This study aims to analyze the determinants affecting Indonesia’s fresh fish exports to its main trading partners, namely China, Japan, Hong Kong, Singapore, and Malaysia, over the period 2012–2023. The research utilizes secondary data sourced from the World Bank and the Central Statistics Agency (BPS). Several independent variables are considered, including the fish production levels in the importing country, the real gross domestic product (GDP) per capita of the importing country, and the total population of the importing country. Panel data analysis was employed to capture the variations across time and countries, with the Random Effect Model (REM) chosen based on the results of the model specification tests. The findings of the analysis indicate that fish production in the importing country exerts a negative and statistically significant effect on Indonesia’s fresh fish exports, suggesting that higher domestic fish production in these countries reduces the need for imports. Conversely, the real GDP per capita of the importing country and its population size were found to have positive and significant impacts on Indonesia’s export volumes. These results highlight that wealthier and more populous nations demonstrate stronger demand for imported fresh fish, including from Indonesia. The implications of this study underscore the importance for Indonesia to continuously improve the quality, safety, and competitiveness of its fresh fish products while also adopting effective marketing and trade strategies targeting countries with high purchasing power and large consumer bases.